The Influence of Interpersonal Communication on Employee Performance at the Tanjung medar District Office, Sumedang Regency - Umi Alawiah, Gina; Kusnidar, Rika; Marliady Nurwan, Teddy (CV. DYOQU PUBLISHING MANAGEMENT, 2025)
Background:The phenomenon studied indicates an imbalance in achievement across several key aspects, with some indicators operating effectively while others require strengthening. This situation impacts the stability of overall performance, necessitating research to understand the interrelationships between factors influencing these results. Aims:This study aims to (1) describe the level of achievement in each variable studied, (2) analyze the relationship between the main variables, and (3) identify which factors need to be improved to strengthen overall performance results. Methods:The research employed a quantitative approach with a descriptive-analytical design. Data were collected using a standardized instrument based on a Likert scale and analyzed using descriptive statistics, correlation and regression tests, to examine the relationships and influences between each variable. All analysis procedures were conducted systematically to obtain an accurate empirical picture. Result:The results of the study indicate that variable Y has more stable performance and is in the good to excellent category, while variable X shows varying performance, with several indicators still in the adequate category. Statistical analysis revealed a positive and significant relationship between the two variables, with a significant influence indicating a significant contribution to performance improvement. Conclusion:The study concluded that variable Y can serve as a reference for strengthening improvement strategies for variable X, given its higher consistency. Although the overall results show positive results, improvements are still needed in indicators of variable X that are still low to ensure optimal and balanced performance. These findings provide an important basis for policy development and further research.